Excessive excretion of cyclic beta-(1,2)-glucan by Rhizobium trifolii TA-1. - Breedveld, M W (1990)
At 25 degrees C, the optimal temperature for growth of Rhizobium trifolii TA-1, extracellular and capsular polysaccharide (EPS and CPS) were the main carbohydrate products synthesized in mannitol-rich medium (10 g of mannitol and 1 g of glutamic acid per liter). In the same medium at 33 degrees C, EPS and CPS production was inhibited, and up to 3.9 g of cyclic beta-(1,2)-glucan was produced during an incubation period of 20 days with a total biomass of 0.55 g of protein. In a medium containing 50 g of mannitol and 10 g of glutamic acid per liter, high cell densities (3.95 g of protein) were obtained at 25 degrees C. This biomass excreted 10.9 g of cyclic beta-(1,2)-glucan within 10 days. Concomitantly, 4.8 g of EPS were synthesized, while CPS production was strongly suppressed. The excreted cyclic beta-(1,2)-glucans were neutral and had degrees of polymerization ranging from 17 to 25, with a degree of polymerization of 19 as the major glucan cycle.